Correlation Between Bitterness Removal And Functional Properties Of Papaya (Carica Papaya L.) Leaves - Kam, Natania; Setiadi, Jacinta Fanya; Hardoko, Hardoko; Rosa, Dela (Department of Technology of Agricultural product (THP) Jambi University, 2022)
The mature papaya leaves are known for its medicinal properties albeit its distinctive bitter taste. In this research 3 different adsorbents; bentonite, activated attapulgite and diatomaceous earth were used to reduce the bitterness of the papaya leaves. The adsorbent treated papaya leaves were then analysed for its sensory evaluation in terms of bitterness intensity and phytochemical compounds which include phenolic, flavonoid, tannin and alkaloid compounds and also antioxidant activity. Papaya leaves treated with bentonite had the most reduced bitterness and application of heat treatment further enhance the efficacy of bitterness removal. However the removal of the bitterness also slightly affected the phytochemical compounds and their functional properties. The leaves treated with bentonite by method of boiling was found to be the most effective method in reducing bitterness, with bitterness intensity score of 0.3 out of the original 11.2, while retaining its phytochemical compound; total phenolic content of 10.699 mg GAE/g extract, total flavonoid content of 1.468 mg QE/g extract, total tannin content of 9.423 mg TAE/g extract, total alkaloid content of 1.363% while retained most of its Antioxidant IC50 of 1001.058 ppm and Antidiabetic properties of 642.231 ppm